Mempelajari Pengaruh Suhu dan Konsentrasi Larutan Garam Terhadap Kadar Telur Asin Ayam - Tharry Yassa; Tamrin Tamrin; Winda Rahmawati; Warji Warji (Jurnal Agricultural Biosystem Engineering, 2023)
Eggs are one of the sources of protein, fat, minerals, and vitamins that are good for the body. Eggs are prone to deterioration in quality caused by physical damage in the form of cracks that can occur during packing, transportation, and storage. One way to prevent damage is by the salting method. Therefore, it is necessary to soak in a salt solution to become salted eggs. The purpose of this study was to determine the effect of the level of salt concentration and temperature during the immersion of eggs in a salt solution to obtain quality salted eggs. The temperatures used in this research of 50ᵒC, 55ᵒC, 60ᵒC, and 65ᵒC, and salt concentrations of 15%, 20%, and 25%. The parameters observed were the measurement of the salt concentration of the salted egg, the changing color in the salted egg yolk, and the taste test for the saltiness of the salted egg. The results obtained by soaking salted chicken eggs at 60ᵒC at a concentration of the salt solution (15%, 20%, 25%) have met the SNI standard quality of 2% because the higher the concentration of salt solution given, the salt content in the egg will also increase. The taste level of saltiness in salted egg chicken obtained an average score of 3 with the taste of egg with salty egg, in which the salt solution increases according to temperature and concentration. The color of the eggs produced at 60ᵒC and 65ᵒC changed from normal yellow to orange-colored yolk eggs. The increase in temperature and the concentration of different salt solutions on the salted egg yolk color is affected by diffusion currents, and It causes the taste of the salted egg to turn salty. Keywords: Chicken Salt Eggs, Salt Solution, Soaking.